A textbook of basic engineering physics - Chakraborty, Amal Kr (Chhaya Prakashani, 2010)
A textbook of basic engineering physics / Chakraborty, Amal Kr. -- Kolkata: Chhaya Prakashani, 2010 530 C426 No. of Copies : 2